Microbial bioconversion of chemical waste effluents from marine gelatin isolation: Production of probiotics under circular economy philosophy - Vázquez, José Antonio; Menduiña, Araceli; Durán, Ana; Nogueira, Margarita; Fraguas, Javier; Pedreira, Adrián; Valcárcel, J. (Journal of Cleaner Production, 2023)
12 pages, 6 figures, 4 tables.-- Under a Creative Commons license The marine gelatin is one of the most interesting biocompounds to recover from fish skin by-products. The initial processes commonly used for gelatin isolation are based on the alkaline and acid washing of skins. These streams, with remarkable levels of proteins, must be efficiently managed and depurated to avoid environmental pollution and to make the gelatin recovery viable. In the current study, we have evaluated the bioconversion of those contaminant gelatin effluents (GE) from tuna, shark, turbot and salmon by means of two probiotic lactic acid bacteria (LAB). These LAB, Lactobacillus plantarum and L. brevis were fermented in batch culture, under controlled conditions, in each of the effluents which simulated the common medium for LAB (Man, Rogosa, Sharp, MRS) but without commercial peptones. In the 50% of the media based on GE, the growth of both bacteria (achieving, for example, 5.2 g/L of L. brevis in alkaline-tuna stream) and lactic acid productions (20 g/L using citric acid-shark stream in L. plantarum) were similar or higher than those observed in MRS. Minimal GE media formulated only with effluents, glucose and salts demonstrated the essential presence of yeast extract as an ingredient to achieve optimal growths. Unstructured mathematical equations modelled accuracy the experimental kinetics of all LAB productions (R2 = 0.92–0.99) and nutrient consumptions (R2 = 0.75–0.99). From an economical viewpoint, productions on effluents reduced around 3 times the costs of production reported in MRS. GE showed to be a good substrate to support LAB productions and the approach exposed here is a sustainable solution to valorize and depurate such wastewaters will help to increase the profitability of fish gelatin industry This research was funded by the projects LIFE-REFISH (European Union's LIFE PROGRAMME under Grant Agreement No. 101047323, LIFE21-ENV-ES-LIFE REFISH), Intramural PIE-CSIC (202130E070) and Xunta de Galicia (Grupos de Potential ...